Supporting Community College Student Success: Evidence from a Randomized Controlled Trial. Issue 1 (2nd January 2023) - Hallberg, Kelly; Hofmeister, Kenny; Bertrand, Marianne; Morgan, Brittany
Abstract: This paper presents findings from a randomized controlled trial studying a comprehensive program designed to support students in achieving their goals. One Million Degrees (OMD) is a nonprofit organization serving community college students in the Chicago metro area that supports students financially, academically, personally, and professionally. Results from our study demonstrate that the randomized offer of a spot in the OMD program leads to a statistically significant and substantively meaningful increase in community college enrollment, persistence, and associate's degree attainment three years after randomization. Applicants who applied while still in high school were less likely to take up the offer of the program than students who were already enrolled in community college, but those high school students who enrolled outperformed their control group peers by a substantially larger margin. Finally, we find the program does not appear to affect the likelihood that students will enroll in a four-year college.